QUALIFIED PRACTICE PERIOD IN PREPARING FUTURE SPECIAL TEACHERS FOR PROFESSIONAL ACTIVITY - Sh.N. Ibadullayeva (American Journals, 2023)
In this article discusses about qualified practice period in preparing future special teachers for professional activity.
Keywords: globalization, professional, modernization, integration, pedagogical education, professional training, philosophical outlook, psychologicalpedagogical diagnosis, skills.